explain basic proportionality theorem of triangle
Answers
Answered by
5
hope it will help uh ....
Attachments:
![](https://hi-static.z-dn.net/files/de9/344e9caaae92b929ca81df53aaaa6c35.jpg)
![](https://hi-static.z-dn.net/files/db3/f49bb1ca56f883e5220adcb423940a47.jpg)
Answered by
0
PM= 3 cm, MQ=9 cm
Now, PM/MQ=3/9=1/3
Also, PN=2 cm, NR=6 cm.
Now, PN/NR= 2/6=1/3
Therefore, PM/MQ=PN/NR
Hence, by the converse of basic proportionality theorem, we have MN parallel to QR.
Now, PM/MQ=3/9=1/3
Also, PN=2 cm, NR=6 cm.
Now, PN/NR= 2/6=1/3
Therefore, PM/MQ=PN/NR
Hence, by the converse of basic proportionality theorem, we have MN parallel to QR.
Similar questions